Written Piagetian Task Instrument: Its Development and Use. - Walker, Richard A.; Hendrix, Jon R.; Mertens, Thomas R. (Science Education, 1979)
The article describes the written Piagetian Task Instruments (PTI) and its application to education. PTI is a set of problems that requires reasoning patterns for solutions via conventional examination or "one-to-one" interview. The objective of this method was to determine the cognitive skills of the individual tested. It evaluates the three basic elements of cognitive reasoning, including propositional logic, combinatorial logic and hypothetico-deductive reasoning. Moreover, PTI is used to determine whether the student is at the level of formal operational thought or at the level of concrete operational thought.